Supervisors' perceptions of postgraduate supervision in a Malaysian public university / Audrey Anak Lembat - Lembat, Audrey (2015)
The high attrition rate coupled with the low completion rate of postgraduates in research programmes has become a global issue of concern. Among the reasons cited for this scenario has been low quality supervision. Even though postgraduate supervision is a much explored area of research in the West and it is just beginning to become an area of exploration in the East and in Asian countries like Malaysia. Therefore the main purpose of this study was to investigate supervisors' different perceptions in postgraduate supervision. To be specific, this study aimed to investigate supervisors' perceptions on their roles and responsibilities, supervisory practices and level of supervisory support provided at various stages of supervision based on variables such as gender, academic qualifications and experience in supervising. Besides that, this study also examined the level of satisfaction of supervisors towards their institutional support and the challenges faced in postgraduate supervision. This study was conducted in one of public universities located in the Klang valley, in Malaysia. Data were collected using a questionnaire which involved 40 postgraduate supervisors and semi-structured interviews with three supervisors specifically. Data were analyzed using descriptive and inferential statistics. The findings revealed that respondents were clear with regards to their roles and responsibilities as a supervisor, they demonstrated good supervisory practices and had provided good support to their students during the supervision process. There were significant differences on supervisors' perceptions towards their roles and responsibilities and supervisory practices based on gender and academic qualifications. Besides that, this study also found that there was a significant difference on supervisors' perceptions towards their level of support based on academic qualifications. However, there were no significant differences on supervisors' perceptions towards their roles and responsibilities, supervisory practices and level of support based on supervision experience. Nevertheless the supervisors felt that institutional support left much to be desired with regards to postgraduate guidelines, procedures and dissemination of information. Likewise, a majority of the supervisors highlighted that institution should provide more support with regards to facilities such as postgraduate rooms, printers and computers for postgraduate students. Additionally, this study found that supervisors faced a number of challenges such as having to cope with students who were ill-prepared for postgraduate study due to their limited reading, writing and research skills. They also felt that students lacked self-discipline and had poor time management skills. Overall, these findings have far-reaching implications as they put forward a critical call for the relevant authorities such as the Ministry of Education, the Graduate Schools as well postgraduate supervisors at institutions of higher learning to relook at the postgraduate supervision and the support provided for postgraduate students at institutional level.